The Citation Economy as a Site of Extraction for Surveillance Publishing - Danielle Colbert-Lewis; lawrence maminta; Kelly McElroy; Graeme Slaght; Mark Swartz (Canadian Journal of Academic Librarianship)
This paper links the ideas of surveillance capitalism and what Jeff Pooley has described as surveillance publishing with that of the citation economy.